The Effect of Organizational Culture on Employee’s Performance and Productivity - Hamkar, Nasir Ahmad; Watanyar, Abdul Basir (Integrated Journal for Research in Arts and Humanities, 2024)
The objective of this research is to investigate the effects of organizational culture on employee performance and productivity, analyze its impact on employee behavior, and explore its benefits for employees and customers. The primary research questions are: (1) What is the impact of organizational culture on employee performance and productivity? (2) What role does organizational culture play in influencing employee performance and productivity? (3) What benefits does organizational culture provide to employees and customers? The hypotheses are: (1) Organizational culture directly impacts employee performance and productivity. (2) Organizational culture plays a vital role in enhancing employee performance and productivity. (3) Organizational culture increases organizational performance, motivates employees to achieve organizational goals, and affects customer loyalty. The research employs a binary system approach and collects data from both primary and secondary sources. Primary data was gathered through a survey of 50 questionnaires distributed to students at Jahan University. Secondary data was sourced from books, websites, and research papers. The findings indicate that organizational culture is practiced within the organization and is perceived as important for improving employee performance. This is supported by the statistically significant contributions of mission and involvement to employee performance. However, consistency and adaptability, while positively correlated with performance, were not statistically significant. The study concludes that not all cultural dimensions significantly contribute to employee performance, suggesting that other unexamined factors may also play a role.